2020
DOI: 10.2196/21623
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Experiences of Patient-Professional Communication Over Patient Portals: Systematic Review of Qualitative Studies

Abstract: Background The popularity of web-based patient-professional communication over patient portals is constantly increasing. Good patient-professional communication is a prerequisite for high-quality care and patient centeredness. Understanding health care professionals’ experiences of web-based patient-professional communication is important as they play a key role in engaging patients to use portals. More information is needed on how patient-professional communication could be supported by patient po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
1
22
0
12
Order By: Relevance
“…HCPs seemed to possess complex perceptions of how digital health affects patient care and, subsequently, the competence requirements of HCPs. Ambivalent perceptions of the effects of digital health have already been previously reported (Odendaal et al 2020 , Laukka et al, 2020 ). The interviewees had a positive outlook on digital health services, either as a whole or specific aspects of digital health, but also recognized the challenges associated with digitalization.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…HCPs seemed to possess complex perceptions of how digital health affects patient care and, subsequently, the competence requirements of HCPs. Ambivalent perceptions of the effects of digital health have already been previously reported (Odendaal et al 2020 , Laukka et al, 2020 ). The interviewees had a positive outlook on digital health services, either as a whole or specific aspects of digital health, but also recognized the challenges associated with digitalization.…”
Section: Discussionmentioning
confidence: 68%
“…HCPs' competence in digitalization has been previously described as consisting of sufficient skills in using digital technology to provide high‐quality ethical patient care, social and communication skills to use digital technology in health prevention, diagnoses and treatment, willingness and motivation to apply digital technology in a professional context, and collegial and organizational support to enhance positive experiences in digitalization (Konttila et al, 2018 ). Previous reports of HCPs' experiences of using digital health services have highlighted both negative and positive aspects, with the negative experiences most commonly related to HCPs' perceptions of their lack of competence in communication with patients through patient portals (Laukka et al, 2020 ), treatment and screening algorithms threatening their clinical competency (Odendaal et al 2020 ) and doubts over whether digital health improves patient care (Ross et al, 2016 ). Barriers such as the poor design of services and careless implementation process as well as lack of access to devices have been identified as inhibiting the use of digital technology in health care and HCPs possess concerns over technology taking time from direct patient care and causing additional stress due to malfunctioning systems (Brown et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, our participants were afraid that patients might share their medical records with an unauthorized person or authority, which could make patients more vulnerable to people or institutions with conflicting interests. A recent review similarly raised this concern regarding patients autonomously handling medical information [ 30 ]. Another study found that a major barrier to redefining work practices of health care professionals through the use of patient portals in hospital care concerned privacy and security [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using digital solutions rather than face-to-face care interactions to deliver personalised care will require a new skillset for both trainees and trainers. 30 The challenges of communicating remotely by telephone or video need to be considered since establishing rapport, obtaining accurate information, conveying attention and empathy to the patient, and accurate understanding may be more challenging. These challenges are particularly relevant given that groups who may most require personalised care tend to also require support in accessing and using digital solutions.…”
Section: Potential Solutionsmentioning
confidence: 99%